Controversies Regarding the Management of Carcinoma of the Thyroid Gland - Begum, T; Siddique, AB; Awal, MA; Khanam, N; Ansari, SM (TAJ: Journal of Teachers Association, 2009)
Of all solid cancers presenting in adults, papillary thyroid cancers generally carry best longterm prognosis. However, very little is understood about the molecular pathogenesis of this neoplasm. Any patient presenting with thyroid nodule-initial work up will be fine needle aspiration cytology (FNAC). Surgical treatment depends on FNA finding, age and clinical presentation. After surgical debulking whole body diagnostic scan should be performed which will follow the need for radioactive iodine (RAI) ablation therapy. Life long assessment after ablation therapy is needed using serum thyroglobulin (Tg) estimation, whole body scan and most recent introduction of rTSH by FDA , USA. doi: 10.3329/taj.v16i1.3903 TAJ June 2003; Vol.16(1): 39-45